Two-stage pricing strategies of a dual-channel supply chain considering public green preference. (January 2021) - Zhang, Chong; Liu, Ying; Han, Guanghua
Highlights: Integrated decisions of pricing and green strategies are explored. Consumers' green preference positively affect supply chain performance. Manufacturer enable to strategically invest on green levels of products. Periodically reviewing price enlarges supply chain profits and market demands. Abstract: In view of the mushroom growth of e-commerce and green production, some enterprises have shifted to provide environment friendly products and made full use of the online sales channel to enhance competitiveness. This paper investigates a dynamic pricing strategy and greening issues for a two-stage dual-channel supply chain containing a manufacturer and a retailer. Furthermore, we discuss pricing and green strategies for members under decentralized and centralized decision scenario. In decentralized decision scenario, two decision strategies are studied and compared. To improve supply chain performance, a cost-sharing contract is proposed. We find the market demand is concave by selling price and the market demand reaches the largest value when selling price equals to reference price. This result shows that the manufacturer should strategically decide the current selling price with respect to the price in the previous period. Sensitivity of consumers to the greening levels, the basic selling price and the greening levels have a positive influence on the performance of the supply chain. Moreover, the products in the centralized decision enjoy higher greening levels than that in decentralized decision scenario. In this study, we contribute to explore the effect of reference price in a dual-channel supply chain management and suggest a two-stage decision strategies to improve supply chain performance with a contract. The limitations and potential future directions are also provided to conclude the study.